Carbon and macronutrient losses during accelerated erosion under different tillage and residue management. (2nd December 2014) - Beniston, J. W.; Shipitalo, M. J.; Lal, R.; Dayton, E. A.; Hopkins, D. W.; Jones, F.; Joynes, A.; Dungait, J. A. J.
Summary There have been many studies on the effects of tillage on erosional losses from soil, but rarely have soil organic carbon (SOC), nitrogen (N) and phosphorus (P) losses been quantified simultaneously during a single erosion event. We applied a simulated rainfall event (70 mm hour−1) to plots within a gently sloping field (6%) in Ohio, USA, on which maize (C4) cultivation had replaced C3 vegetation several decades earlier. The plots were under different tillage management: (i) no till (NT100) for 42 years; (ii) NT100 plots from which 50% (NT50) or (iii) 100% (NT0) of crop residues were removed annually for 8 years; (iv) NT100 plots tilled 24 hours previously (TNT); and (v) conventional tillage (CT) for 28 years. Relationships between SOC, N and P concentrations and natural abundance 13C : 15N stable isotope values in the topsoils and sediments suggested that eroded SOC and TN were associated with the erosion of soil organic matter, whilst P losses were driven by the transport of the mineral fraction. Stable 13C isotope analyses revealed that tillage and residue removal both increased the proportion of older (C3), rather than new (C4, maize‐derived), SOC in eroded sediments. This study therefore demonstrated that a single tillage event after 42 years of continuous no‐till caused larger erosional fluxes than 8 years of continuous removal of all maize residues, and that long‐term conventional tillage resulted in the loss of a greater amount of older (> 28 years) SOC in eroded sediments, compared with continuous NT management.